Socio-Economic Impacts of Rivers State Government Ring Road Project on Residents of Port Harcourt Municipality - Weje, Innocent Ikezam; Obiolo Kalu A.O.; Nordee Barida (International Journal of Rural and Regional Development, 2025)
As nations strive towards improving the socio-economic well-being of its citizens, efficient transportation system in the form of ring roads have become a desideratum for reducing traffic congestion and enhancing movement of goods and services. The paper examines the impacts a ring road can have on residents of project area with emphasis on Port Harcourt. The Hazard and Effect Management Process (HEMP) technique developed by SHELL was used to examine the socio-economic impacts of the ring road on residents of the study area. Findings showed that, the ring road has both positive and negative impacts on residents in the area. The identified positive impacts are: improved transportation networks and access (11.5%); boost to local businesses (11.4%); improved transport infrastructure (11.3%); and reduced travel time (10.6%). Other positive benefits are increase in property values (10.2%); job creation (8.2%); enhanced quality of life (8.8%); and increased connectivity between settlements (7.9%). Of the negative impacts of the ring road, displacement of residents ranks highest (30.7%), followed by environmental pollution (23.3%), infrastructure damage (18.9%), traffic congestion and delays (13.9%), and inadequate compensation (13.3%). While, the construction of the ring road project has the potential to improve transportation system and reduce congestion in the study area, the associated negative concerns should be addressed to mitigate their impacts on residents and promote project acceptance for sustainability. Enhancing transparency, increasing community participation, and providing compensation for those negatively affected are key steps to ensuring that the project delivers on its promise to improve both infrastructure and the socio-economic well-being of residents.
Keywords: Ring road; Sustainability; development; infrastructure; socio-economic impact; transport connectivity